Optimised design of isolated industrial power systems and system harmonics - Maticevic, Stjepan (Curtin University, 2011)
This work has focused on understanding the nature and impact of non-linear loads on isolated industrial power systems. The work was carried out over a period of 8 years on various industrial power systems: off-shore oil and gas facilities including an FPSO, a wellhead platform, gas production platforms, a mineral processing plant and an LNG plant. The observations regarding non-linear loads and electrical engineering work carried out on these facilities were incorporated into the report.A significant literature describing non-linear loads and system harmonics on industrial power systems was collected and reviewed. The literature was classified into five categories: industrial plants and system harmonics, non-linear loads as the source of current harmonics, practical issues with system harmonics, harmonic mitigation strategies and harmonic measurements.Off-shore oil and gas production facilities consist of a small compact power system. The power system incorporates either its own power generation or is supplied via subsea cable from a remote node. Voltage selection analysis and voltage drop calculation using commercially available power system analysis software are appropriate tools to analyse these systems. Non-linear loads comprise DC rectifiers, variable speed drives, UPS systems and thyristor controlled process heaters. All nonlinear loads produce characteristic and non-characteristic harmonics, while thyristor controlled process heaters generate inter-harmonics. Due to remote location, harmonic survey is not a common design practice. Harmonic current measurements during factory acceptance tests do not provide reliable information for accurate power system analysis.A typical mineral processing plant, located in a remote area includes its own power station. The power generation capacity of those systems is an order of magnitude higher than the power generation of a typical off-shore production facility. Those systems comprise large non-linear loads generating current and voltage interharmonics. Harmonic measurements and harmonic survey will provide a full picture of system harmonics on mineral processing plants which is the only practical way to determine system harmonics. Harmonic measurements on gearless mill drive at the factory are not possible as the GMD is assembled for the first time on site.LNG plants comprise large non-linear loads driving gas compressor, however those loads produce integer harmonics. Design by analysis process is an alternative to the current design process based on load lists. Harmonic measurements and harmonic survey provide a reliable method for determining power system harmonics in an industrial power system.